Tumor-Associated Macrophage Targeting of Nanomedicines in Cancer Therapy - Xuejia Kang; Yongzhuo Huang; Huiyuan Wang; Sanika Jadhav; Zongliang Yue; Amit K. Tiwari; R. Jayachandra Babu (MDPI AG, 2023)
The tumor microenvironment (TME) is pivotal in tumor growth and metastasis, aligning with the "Seed and Soil" theory. Within the TME, tumor-associated macrophages (TAMs) play a central role, profoundly influencing tumor progression. Strategies targeting TAMs have surfaced as potential therapeutic avenues, encompassing interventions to block TAM recruitment, eliminate TAMs, reprogram M2 TAMs, or bolster their phagocytic capabilities via specific pathways. Nanomaterials including inorganic materials, organic materials for small molecules and large molecules stand at the forefront, presenting significant opportunities for precise targeting and modulation of TAMs to enhance therapeutic efficacy in cancer treatment. This review provides an overview of the progress in designing nanoparticles for interacting with and influencing the TAMs as a significant strategy in cancer therapy. This comprehensive review presents the role of TAMs in the TME and various targeting strategies as a promising frontier in the ever-evolving field of cancer therapy. The current trends and challenges associated with TAM-based therapy in cancer are presented.